Faktor-Faktor Penyebab Covid 19 pada Pegawai UPTD Lab Kesda Dinas Kesehatan Provinsi Lampung Tahun 2022: The Factors that Cause Covid 19 in UPTD Lab Kesda Employees at the Lampung Provincial Health Office - Ampera Indah Tanti; Handrika Permatawati; Luthfiatuzzaqiyah Rasyid; Reni Yusepa; Ramadhan R Firdaus; Duwian Liwanty Manulang (Jurnal Surya Medika (JSM), 2022)
Efforts to stop the spread of COVID-19 require the full cooperation of the wider community. Our ability to learn comes from observing the world using our five senses. The most significant factor in shaping a person's behavior is also knowledge. This study aims to determine the factors that cause Covid 19 in UPTD LAB KESDA employees at the Lampung Provincial Health Office. quantitative research, cross-sectional method, and analytic survey, and 43 respondents are the population and sample for this study. The sampling strategy was purposive sampling, and univariate and bivariate data analysis was performed using chi-square. 23 people (53.5%) have a high workload at the LABKESDA Health Office of Lampung Province. The level of stress in the LABKESDA Health Office of Lampung Province, as many as 24 people (55.8%) experienced stress. Immunity in LABKESDA Lampung Provincial Health Office as many as 27 people (62.8%) have low immunity. The chi-square test obtained a “p-value of 0.000 (<0.05),” which means that there is a relationship between workload and the incidence of covid 19 in the UPTD LAB KESDA Lampung Provincial Health Office. The chi-square test obtained a “p-value of 0.001 (<0.05),” which means that there is a relationship between stress levels and the incidence of covid 19 in the UPTD LAB KESDA Lampung Provincial Health Office. The chi-square test obtained a “p-value of 0.000 (<0.05),” which means that there is a relationship between immunity and the incidence of covid 19 in the UPTD LAB KESDA Lampung Provincial Health Office.